Modelling recycling for the life cycle assessment of perovskite/silicon tandem modules - Wang, Lu; Oberbeck, Lars; Marchand Lasserre, Mathilde; Perez-Lopez, Paula (EPJ Photovoltaics, 2024)
With the massive growth of the global capacity of photovoltaics (PV) over the last decade, the PV waste is expected to increase dramatically in the near future. Having potential to reduce the use of raw materials and preserve natural resources, PV recycling is attracting more and more attention. This being said, the environmental impacts over the life cycle of PV technologies, including the end-of-life (EoL) stage, should be evaluated carefully. Life cycle assessment (LCA) is currently the most common methodology to assess the potential environmental impacts of a product throughout its entire life cycle. However, the modelling of recycling in LCA has always been a challenge and no consensus has yet been reached, since the treatment of recycling does not only involve an EoL management of waste, but also the production of recycled material. Perovskite on silicon tandem is a widely investigated emerging PV technology having the potential to overcome the power conversion efficiency (PCE) limit of the single-junction crystalline silicon technology. The EoL modelling seems more challenging in the case of emerging technologies for which the EoL is more uncertain than for established technologies. In this article, six common and important approaches of EoL modelling in LCA were applied to future perovskite/silicon tandem modules to analyze the effect of the different EoL modelling approaches on the LCA results. The aim was to identify the most suitable methodological approaches to account for recycling, when modelling the life cycle of PV modules. The environmental performance of perovskite/silicon tandem modules was assessed over their life cycle and expressed in terms of impacts per m 2 of module. After testing the six EoL modelling approaches and comparing the LCA results, the EoL modelling choice was found to lead to non-negligible differences. For example, in terms of climate change, the impact of the tandem modules ranges from 45 to 59 kg CO 2 -eq/m 2 . Among the six EoL modelling options, the approaches of simple cut-off and cut-off with economic allocation are more oriented towards the promotion of high rates of recycled material integrated as an input to the assessed product among industrial actors, while the approach of closed-loop allocation provides incentives to maximize the ratio of recycling at the EoL, regardless the initial ratio of recycled content within the product. Some approaches such as the circular footprint formula (CFF) tend to provide both incentives to increase the content of recycled input material in the manufacturing of the product and the recycling ratio at the EoL of such product. After applying the different alternatives, a set of recommendations to select the relevant EoL modelling approaches are provided: 1) the CFF is recommended as a representative approach due to its wide applicability, tending to provide an intermediate result and reflecting the characteristics of materials; 2) sensitivity analysis should be applied to check the robustness of the results, 3) the cut-off approach and the closed-loop allocation should be used at least for the sensitivity analysis.